Управління інноваційними проєктами у контексті змін у сучасному бізнес-середовищі. - Kyfyak, Viktoria; Унгурян, Ольга (ПРОБЛЕМИ СИСТЕМНОГО ПІДХОДУ В ЕКОНОМІЦІ, 2024)
У статті розглядаються сучасні підходи до управління проектами, зокрема методи відбору проектів у контексті інноваційної діяльності. Автори аналізують основні критерії та методи, які використовуються для ефективного відбору проектів, що сприяють інноваціям. Основна увага приділяється порівнянню різних методологій та їх впливу на успіх проектів. Наведені приклади з практики показують, як правильний вибір проектів може сприяти досягненню стратегічних цілей організації. Окрім того, стаття досліджує роль управлінських рішень у процесі відбору та реалізації інноваційних проектів. Автори також розглядають використання сучасних інформаційних систем для підтримки процесу прийняття рішень. Стаття буде корисною для фахівців у сфері управління проектами, які прагнуть підвищити ефективність своїх організацій за допомогою впровадження інноваційних рішень.
INNOVATION PROJECT MANAGEMENT IN THE CONTEXT OF CHANGES IN THE MODERN BUSINESS ENVIRONMENT
In the backdrop of war, the significance of project management is amplified. Conflict scenarios present their own set of obstacles for organizations and governmental bodies, compelling them to efficiently allocate resources and oversee projects to ensure security, respond to unexpected eventualities, and rehabilitate damaged infrastructure. Within this framework, the article delves into how contemporary project management methodologies can aid in addressing the intricate challenges posed by war, particularly through the judicious selection and execution of innovative projects. The authors scrutinize diverse strategies for project selection, with a focus on their potential impact on fostering innovation. They dissect the primary criteria and methodologies employed in this process, juxtaposing their efficacy in attaining the organization’s strategic objectives. It is pivotal to assess the ramifications of various project selection approaches on their ultimate success, a factor of paramount importance in scenarios characterized by limited resources and time constraints, such as during wartime. The practical instances cited in the article elucidate how astute project selection can advance an organization’s strategic agenda even amidst adversity. Furthermore, the authors explore the role of managerial decisions in guiding the selection and execution of innovative projects, thereby enabling a lucid delineation of strategic imperatives and the adoption of optimal pathways towards goal attainment. Additionally, the article underscores the utilization of contemporary information systems to underpin the decision-making process, a facet further accentuated in military environments where the rapidity of response and precision of information can sway critical outcomes. In summation, the article emerges as a valuable repository of insights for project management specialists, particularly in wartime scenarios, seeking to enhance their organizations’ efficacy through the integration of innovative solutions and streamlining project management protocols. Keywords: project management, project selection, innovation, project management, selection methods.
Keywords: Ключові слова: управління проектами, відбір проектів, інновації, управління проектами, методи відбору